2015
DOI: 10.24126/jobrc.2015.9.2.439
|View full text |Cite
|
Sign up to set email alerts
|

PCR Detection of Some ESBLs (bla) Genes in Pseudomonas aeruginosa Isolated from Burn’s Units in Bagdad Hospitals

Abstract: Multi drug resistant (MDR) and Extended Spectrum Beta Lactamase (ESBLs) of Pseudomonas aeruginosawere detected. Pseudomonas aeruginosa is a bacterium responsible for severe infections in burn’s units,plasmid DNA analysis and encoded many types of genes responsible for beta-lactamases. To determine thetype of genes responsible for beta-lactam broad spectrum in P. aeruginosa strains isolated from 100 swabsof burn’s units environment, using a molecular methods (PCR) by primers specific to ESBLs (bla ) genesoxacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In this study the percentage of resistance for Cephems (Cephalosporin IV) including (Cefepime and Ceftazidime) Cefepime agree with [32] rate resistance of cefepime was (100%) and In this study disagree with [33] the rate was (23.5%) resistance. In this study the percentage of resistance for Ceftazidime agree with the results of [34] in Basrah, that P. aeruginosa were resistant to ceftazidime, (100%).…”
Section: Antibiotic Susceptibility Of P Aeruginosamentioning
confidence: 48%
“…In this study the percentage of resistance for Cephems (Cephalosporin IV) including (Cefepime and Ceftazidime) Cefepime agree with [32] rate resistance of cefepime was (100%) and In this study disagree with [33] the rate was (23.5%) resistance. In this study the percentage of resistance for Ceftazidime agree with the results of [34] in Basrah, that P. aeruginosa were resistant to ceftazidime, (100%).…”
Section: Antibiotic Susceptibility Of P Aeruginosamentioning
confidence: 48%
“…As well as, Nasih et al [2014] recorded (17%) P. aeruginosa from the patients. Another study showed that (38%) P. aeruginosa isolates among 100 burn samples in Baghdad hospitals 21 . P. aeruginosa is currently one of the major bacterial pathogens responsible for nosocomial infections and due to resistance to various antibiotics the treatment of these infections has become very diffi cult.…”
Section: Discussionmentioning
confidence: 99%